Stereoselective syntheses of (+)-proto, (-)-gala quercitols and carba-L-rhamnose from D-(-)-quinic acid - Murugan, A. Vadivel; Yadav, A. K.; Gurjar, M. K. (Tetrahedron Letters, 2005)
Efficient syntheses of (+)-proto, (-)-gala quercitols and carba-L-rhamnose front D-(-)-quinic acid are described. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: (+)-proto quercitol; (-)-gala quercitol; carba-L-rhamnose; cyclohexanepentols; D-(-)-quinic acid; stereoselectivity

Direct shoot organogenesis and plant regeneration from hypocotyl explants in selected genotypes of Leucaena leucocephala - a leguminous pulpwood tree - Sirisha, V. L.; Prashant, S.; Ranadheer, D.; Ramprasad, P.; Shaik, N. M.; Arha, Manish; Gupta, S. K.; Srivastava, Sarneer; Yadav, A. K.; Kulkarni, P. S.; Othalathara U. Abhilash; Khan, Bashir Mohammad; et al. (Indian Journal of Biotechnology, 2008)
An efficient in vitro plant regeneration system in subabul (Leucaena leucocephala), a leguminous pulp wood tree species, was established. The induction of shoots was achieved from selected elite clones of subabul K-8, K-636 and also wild type on MS medium supplemented with 2% sucrose and different concentrations (0.88 to 24.6 mu M) of plant growth regulators (BA, Kn, 2iP & TDZ). The best medium for shoot regeneration was MS with 22.2 mu M BA (5 shoots per explant), followed by 22.7 mu M TDZ (4.6 shoots per explant). Addition of putriscine (9.3 mu M) to MS medium containing 22.2 mu M BA enhanced the number of multiple shoots to 7-8 but not the frequency of response. Shoot initials (measuring 1 cm) when separated and transferred on to MS medium containing 1.4 mu M GA(3) elongated to 2-5 cm in 15.20 d with 80% frequency. The per cent frequency of shoot differentiation was almost identical in the genotypes K-8 and K-636 but it differed significantly from the wild type. Leaf yellowing and abscission in all the genotypes was curtailed by supplementing the medium with 685 mu M glutamine or 540 mu M adenine. The excised shoots were transferred to root regeneration media containing 2.46 and 4.98 mu M IBA or 2.6 and 5.3 mu M NAA. Root regeneration was noticed with 100% frequency in all the three genotypes in presence of IBA or NAA. Plantlets were transferred successfully to the pots with 70% survival rate with no visible morphological variations. The protocol can be utilized for mass propagation and genetic transformation studies of this important pulpwood species.
Keywords: hypocotyl explants; Leucaena lucocephala; pulpwood leguminous tree; shoot organogenesis

Electronic structure-sunlight driven water splitting activity correlation of (Zn1-yGay)(O1-zNz) - Rajaambal, Sivaraman; Yadav, A. K.; Jha, Shambhu Nath; Bhattacharyya, Dibyendu; Gopinath, Chinnakonda S. (Physical Chemistry Chemical Physics, 2014)
(Zn1-yGay)(O1-zNz) (y <= 0.10; z <= 0.15) solid solutions have been investigated for their electronic structure and visible light photocatalytic activity, and a correlation was found between them. (Zn1-yGay)(O1-zNz) with ZnO as the major component have been synthesized by a solution combustion method in 10 minutes using simple raw materials. The local structures of Zn K edge and Ga K edge, and changes in the chemical environment with the incorporation of Ga and N in ZnO were determined by EXAFS study. EXAFS and XRD results suggested the dissolution of GaN in the ZnO lattice. The homogeneity of the solid solution was demonstrated from HRTEM studies. Photoluminescence studies revealed the creation of a new band at the top of the ZnO valence band (VB), and thus the broadening of the VB of (Zn1-yGay)(O1-zNz) or a decrease in the band gap was attributed to the origin of visible light absorption. UV-Vis spectral studies showed light absorption up to 550 nm, which directly supports the VB broadening. Predominant oxygen vacancies and high photocorrosion observed for ZnO were fully suppressed for (Zn1-yGay)(O1-zNz) , indicating the minimization of defects, and thus more sustainability under irradiation conditions. The bare solid solution exhibited reasonable and promising activity for solar hydrogen evolution and photoelectrochemical current generation at 0 V. The present work explained factors such as the preparation method, single phase structure with the stabilization of integral parts, homogeneity in the structure, compensation of oxygen vacancies, and suppression of the density of recombination centres that play a pivotal role in realizing solar energy harvesting.

Spectroscopic evidences for the size dependent generation of pd species responsible for the low temperature CO oxidation activity on Pd-SBA-15 nanocatalyst - Soni, Yogita; Pradhan, Sumanta; Bamnia, Mahesh K.; Yadav, A. K.; Jha, S. N.; Bhattacharyya, D.; Khan, Tuhin Suvra; Haider, M. A.; Vinod, C. P. (Applied Catalysis B-Environmental, 2020)
A comprehensive size dependent CO oxidation activity has been demonstrated for Pd-SBA-15 catalysts with Pd NPs of varying sizes such as 1-2, 4-6 and 7-10 nm. Pd-SBA-15 catalyst with smallest sized NPs (Pd-S-N) has been synthesized by modified deposition precipitation method recently developed in our lab. Pd-S-N catalyst (reduced at 400 degrees C) demonstrated CO oxidation activity with lower light off temperature (50 degrees C), clearly one of the best reported for a Pd-silica system. A detailed XPS and in-situ DRIFTS analyses further supported by XAS and DFT calculations reveal the presence of easily decomposable highvalent Pd-oxide on co-ordinatively unsaturated Pd sites (Pdcus). Weak binding of CO on Pdcus sites in small Pd NPs leaving sites for oxygen activation is attributed to the low temperature activity of Pd-S-N for CO oxidation.
Keywords: CO oxidation; high-valent Pd species; Pd nanoparticles; SBA-15; under coordinated Pd atoms